2020
DOI: 10.1016/j.syapm.2019.126052
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Brenneria goodwinii and Gibbsiella quercinecans, associated with acute oak decline, in rainwater and forest soil

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…As sampling was done only once, it is necessary to repeat sampling from symptomatic and asymptomatic oak trees and isolate bacteria to find out if they are significant in contribution to AOD development. Especially, it was shown that B. goodwinii is oak endosymbiont which cannot survive outside the host plant for a long time, and which can change in a viable but non-culturable state if the ambient conditions are inappropriate (Pettifor et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As sampling was done only once, it is necessary to repeat sampling from symptomatic and asymptomatic oak trees and isolate bacteria to find out if they are significant in contribution to AOD development. Especially, it was shown that B. goodwinii is oak endosymbiont which cannot survive outside the host plant for a long time, and which can change in a viable but non-culturable state if the ambient conditions are inappropriate (Pettifor et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of these bacterial sequence data in DNA extracted from leaves does not distinguish between bacteria living as endophytes, epiphytes or present due to rain or insect dispersal. Pettifor et al [35] found that rainwater, and to a lesser extent, soil, could act as a reservoir for G. quercinecans but not for B. goodwinii. This evidence indirectly suggests that B. goodwinii is an endosymbiont, but G. quercinecans may have a different niche [35].…”
Section: Discussionmentioning
confidence: 99%
“…Pettifor et al [35] found that rainwater, and to a lesser extent, soil, could act as a reservoir for G. quercinecans but not for B. goodwinii. This evidence indirectly suggests that B. goodwinii is an endosymbiont, but G. quercinecans may have a different niche [35]. We found R. victoriana and L. britannica to be more widespread than either G. quercinecans or B. goodwinii, which could suggest a wider dispersal in the environment for these two species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory experiments assessing the ability of B. goodwinii and G. quercinecans to survive in water and soil showed that G. quercinecans, although not culturable from soil, was detectable using qPCR up to 84 days after inoculation in both rainwater and soil. Brenneria goodwinii was not able to survive in either environment suggesting that it is an endophytic or epiphytic plant pathogen, whereas G. quercinecans is more generalist and able to survive in environmental reservoirs [35]. Recent unpublished research into potential transmission mechanisms of AOD found B. goodwinii and G. quercinecans on samples of leaves of both healthy and symptomatic trees and at AOD affected and unaffected sites (Emma Bonham, personal communication 20 th June 2019).…”
Section: Introductionmentioning
confidence: 99%